Response of three soybean cultivars to three spacings and three seeding densities, in Pelotas, RS - Junior, Francisco de Jesus Vernetti; Vernetti, Francisco de Jesus (Pesquisa Agropecuaria Brasileira, 2014)
This work aimed to determine the effects of cultivars, row width, and distance between plants in a row (row seeding rate), as well as their respective interactions, on the yield of soybeans (Glycine max (L.) Merrill), in the 1977/78 crops season, a 33 factorial experiment, with four replicates, arranged in a randomized blocks design, was planted at the State Experimental Research Unit (UEPAE), Pelotas, RS. Cultivar, row width and row seeding rate and their interactions were evaluated; all were significant at the 1% level of probability. IAS 4 had the highest yield, significantly superior to the IAS 2 yield. IAS 2 showed the plant canopy most appropriate to intragenotypic competition under water stress conditions, whereas Hardee did not show the same genetic potencial as IAS 2 and IAS 4 to maintain a fair yield stability when the area available for plant growth was increased. The highest populations gave the highest yields and for Hardee the highest degree of lodging. The highest yield was obtained with 0,40 m row/width and 25 plants per meter of row. At the lowest row seeding rate (15 plants/meter) row width differences (0,40 m or 0,60 m or 0,80 m) did not affect yield.